Characterization of Patients with Human Immunodeficiency Virus in the Area I in Cienfuegos from 1988 to 2011 - Graciela Caridad Cabrera Acea; Belkis Vicente Sánchez; Lietter Aguilar Jure; Yadenis Cardoso Pérez; María del Rosario Sánchez Soto; Cinthya Gómez Cabrera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Background: over 60 million people worldwide have been affected by the human immunodeficiency virus. Globally, it is the fourth leading cause of death; therefore it is considered a global emergency. Objective: to characterize patients with the human immunodeficiency virus. Methods: a retrospective, descriptive study was conducted involving 21 patients diagnosed with human immunodeficiency virus/AIDS in the Area I in Cienfuegos from 1988 to 2011. The variables analyzed included: age, sex, year of diagnosis, People's Council they belong to, sexual orientation, educational level, occupation, presence of opportunistic diseases and antiretroviral treatment. Results: groups aged 25 to 34 and 35 to 44 years (33, 33 %) predominated; 90, 48 % of the patients were males with a ratio of 9,5:1; 38,10 % was diagnosed from 2009 to 2011, 71, 4 % of the cases belonged to the Historic Center; 57, 14 % were men who had sex with men; those who completed high school and university studies accounted for 66,66 % of the cases. Workers prevailed (57, 14 %); only 14, 29 % suffered from opportunistic diseases and 52, 4 % was undergoing antiretroviral treatment. Conclusions: infection increased in the last five years, particularly in most sexually active age groups; it was more common in men who have sex with men. More than half of the patients receive antiretroviral treatment.